2012
DOI: 10.1016/s2255-4971(15)30347-5
|View full text |Cite
|
Sign up to set email alerts
|

Results of Surgical Treatment of Denerative Arthropathy of the Rotator Cuff Using Hemiarthroplasty- Cta®

Abstract: Objective: To assess results of CTA® partial shoulder arthroplasty for treatment of degenerative arthropathy of the rotator cuff. Methods: Between December 2006 and June 2009, 23 shoulders of 23 patients were submitted to CTA® type partial shoulder arthroplasty for treatment of arthropathy secondary to rotator cuff injury. Post-operative follow up time ranged from 6 to 35 months. Mean age was 74.1 years. Patients were predominantly female, representing 78.3% of cases. The right limb was affected in 18 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…During a mean follow-up of 1.6 years, there were improvements in the clinical parameters and UCLA score, as described in the paper by Brasil Filho et al 14 These patients were evaluated prospectively in the present study after a mean follow-up of 5.4 years.…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…During a mean follow-up of 1.6 years, there were improvements in the clinical parameters and UCLA score, as described in the paper by Brasil Filho et al 14 These patients were evaluated prospectively in the present study after a mean follow-up of 5.4 years.…”
Section: Methodsmentioning
confidence: 73%
“…Additional examinations, such as computed tomography and magnetic resonance imaging, are not necessary for diagnosing arthropathy of the rotator cuff, but they help in making preoperative assessments to analyze the bone stock and the conditions of the rotator cuff, such as fatty degeneration 12, 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it needs an intact functioning motor, such as the deltoid muscle and the axillary nerve. (1) Among 16 patients submitted to hemiarthroplasty for treatment of arthropathy due to lesion of the rotator cuff, Field et al (9) found that four out of six patients with unsatisfactory results had been submitted to previous acromioplasty, with release of the coracoacromial ligament.…”
Section: Discussionmentioning
confidence: 99%
“…The term “degenerative arthropathy of the rotator cuff” was first described by Neer, in 1983, and means the collapse of the glenohumeral joint secondary to a massive chronic lesion of the rotator cuff, causing insufficiency of the rotator cuff, rising (cranialization) of the humeral head, joint destruction, synovial fluid alterations, subchondral cysts, flattening of the greater tubercle, osteophytes, acetabularization of the coracoacromial arch, and osteopenia; (1-4) the first three changes were present in all patients. (5) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation